A new angiotensin-converting enzyme inhibitor from Peperomia pellucida (L.) Kunth - Ahmad, Islamudin; Ambarwati, Neneng Siti Silfi; Elya, Berna; Omar, Hanita; Mulia, Kamarza; Yanuar, Arry; Negishi, Osamu; Mun'im, Abdul (Medknow Publications, 2019)
Objective: To isolate, identify, and evaluate a new angiotensin-converting enzyme inhibitor from Peperomia pellucida (L.) Kunth herbs. Methods: A dried sample of Peperomia pellucida herb was successively macerated with n-hexane and ethyl acetate. The ethyl acetate extract solution was evaporated to obtain the crude extract. Vacuum liquid column chromatography and thin layer chromatography were performed to obtain two pure compounds. Then, both compounds were elucidated and identified using the spectroscopic method. Angiotensin-converting enzyme inhibitory activity studies of both compounds were determined using angiotensin-converting enzyme kit WST-1 with spectrophotometer microplate reader 96-well at 450 nm wavelength. Results: Two bioactive compounds were successfully isolated from Peperomia pellucida herb, including a new compound of 2,3,5-trimethoxy-9-(12,14,15-trimethoxybenzyl)-1H-indene and pellucidin A. Both compounds demonstrated angiotensin-converting enzyme inhibitory activity, with IC50 values of 72 μM (27.95 μg/mL) and 11 μM (4.4 μg/mL), respectively. Conclusions: In the present study, two active angiotensin-converting enzyme inhibitors were successfully isolated and purified from Peperomia pellucida which is used as an antihypertensive in traditional medicine, and support its use as an angiotensin-converting enzyme-inhibiting drug. © 2019 Wolters Kluwer Medknow Publications. All rights reserved.